Antioxidant Activities of Chicken Peptide‐Maillard Reaction Products (CP‐MRPS) Derived from Chicken Peptides and d‐Glucose System. Issue 2 (1st August 2016) - Bai, Weidong; Wang, Qin; Zeng, Xiaofang; Fu, Jiayin; Liu, Yaoru; Dong, Hao
Abstract: Chicken peptide‐Maillard reaction products (CP‐MRPs) were prepared by Maillard reaction (MR) process of chicken peptide and antioxidant activity of CP‐MRPs was evaluated by means of reducing power, DPPH radical scavenging activity, hydroxyl radical scavenging activity and chelating activity on ferrous ion. Meanwhile, the effects of MR conditions (e.g., concentration, reaction time, ratio of glucose to peptide and temperature) on antioxidant activity of CP‐MRPs were also investigated. The results showed that browning intensity of CP‐MRPs increased significantly ( P < 0.05) with reaction time increase. CP‐MRPs possessed greater ( P < 0.05) reducing power and DPPH radical scavenging activity than those of Vc, while CP‐MRPs did not exhibit hydroxyl radical scavenging activity and chelating activity on ferrous ion. The reducing power of CP‐MRPs increased with increasing reactants concentration, reaction time as well as temperature. DPPH radical scavenging activity did not have a distinct variation when treated along with different temperature and reaction time. Practical Applications: Maillard reaction products (MRPs) have been reported to contribute not only to the taste, aroma and color, but also to antioxidant potential of stored and processed foods. However, little work has been done on the antioxidant activity of chicken peptide and chicken peptide‐Maillard reaction products (CP‐MRPs) in the Maillard reaction (MR) of chicken peptides andd ‐glucose system. The results obtained in this work could provide indicative data for the chicken‐flavor seasoning industry on how the reaction conditions in MR influences the antioxidant activities of CP‐MRPs.